(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف هذا البحث الى دراسة أثر الأزمة في سورية في جامعة تشرين خلال الفترة (2005-2015) وذلك من خلال دراسة أثر الأزمةفي كل من عدد الطلاب المسجلين، عدد الطلاب الخريجين، عدد رسائل الدراسات العليا المسجلة، والمنجزة، وعدد أعضاء الهيئة التعليمية، ونصيب أعضاء الهيئة التعليمية من الطلاب، ونسبة الخريجين من الطلاب. وتم التوصل لعدة نتائج أهمها أدت الأزمة في سورية لزيادة كل من الطلاب المسجلين، وعدد رسائل الدراسات العليا المسجلة، والمنجزة، واعداد أعضاء الهيئة التعليمية، ونصيب أعضاء الهيئة التعليمة من الطلاب في جامعة تشرين، بينما لم يكن هناك أثر للأزمة على عدد الطلاب الخريجين كذلك على نسبة الخريجين من الطلاب. This study aims at studying the impact of the crisis in Syria at Tishreen University during the period 2005-2015 through studying the impact of the crisis in the number of enrolled students, the number of graduate students, the number of registered and completed graduate studies, the number of faculty members, Faculty members of students, and the proportion of graduates of students. A number of results were achieved, the most important of which was the crisis in Syria to increase the number of registered students, the number of registered and completed graduate letters, the preparation of faculty members and the share of teaching staff members in Tishreen University. Percentage of graduates of students.